Analisis Pembelajaran Pendidikan Pancasila Ditinjau Dari Penguatan Profil Pelajar Pancasila Fase B - Atharicia Ramadhani Cinta Suwasono; Sri Marmoah (Didaktika Dwija Indria, 2025)
This research has a goal to know about the way how a teacher strengthens a Pancasila student profile through pancasila education learning. This research uses a qualitative approach, using observe, interview, and documentation techniques while learning. Subjects of this research are the teacher and students of 4th grade in Muhammadiyah 15 Sumber elementary school. After collecting data, data would be analysed using interactive analysis technique. Results of this research showed Pancasila students profile’s dimensions had strengthened while the learning process were beliefs and fear of God and also noble manners, global diversity, collaborative work, independent, and creative. On several points during the learning process, the teacher hadn’t been consistent to invite students to pray together. Pancasila student profile’s dimension that was inconsistently strengthened was critical reasoning, because the teacher only gave triggering questions for cultivating student engagements. Teacher should provide learning process with all of the Pancasila student profile’s dimension, because moral capabilities in this increasingly modern era are needed to prepare students, so they won’t be destroyed by the increasingly modern age.